Re-introducing The Concept of the Mind, a Foreword - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Re-introducing The Concept of the Mind, a Foreword." In The Concept of the Mind, by Gilbert Ryle, viii-xix. New York: Penguin Classics, 2000.